2005
DOI: 10.1002/bit.20713
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the transglycosylation activity of α‐galactosidase from Bifidobacterium adolescentis DSM 20083 by site‐directed mutagenesis

Abstract: The alpha-galactosidase (AGA) from Bifidobacterium adolescentis DSM 20083 has a high transglycosylation activity. The optimal conditions for this activity are pH 8, and 37 degrees C. At high melibiose concentration (600 mM), approximately 64% of the enzyme-substrate encounters resulted in transglycosylation. Examination of the acceptor specificity showed that AGA required a hydroxyl group at C-6 for transglycosylation. Pentoses, hexuronic acids, deoxyhexoses, and alditols did not serve as acceptor molecules. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
2
28
0
2
Order By: Relevance
“…Similar results were found for the heterologously produced enzyme [123,125,126]. In contrast to the preferred formation of 1 6 linkages during the transfer reaction, Leder et al [122] showed that 1 3 linkages are hydrolyzed at a higher rate than 1 6 linkages.…”
Section: A-galacto-oligosaccharides and Galactomannansupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results were found for the heterologously produced enzyme [123,125,126]. In contrast to the preferred formation of 1 6 linkages during the transfer reaction, Leder et al [122] showed that 1 3 linkages are hydrolyzed at a higher rate than 1 6 linkages.…”
Section: A-galacto-oligosaccharides and Galactomannansupporting
confidence: 75%
“…For bifidobacteria only one attempt is reported. In this case the transglycosylation properties of a-galactosidase from B. adolescentis were changed by sitedirected mutagenesis [125]. The highest increase in transglycosylation activity obtained was 16% for one single mutant, whereas most of the other single mutants showed an increase of only 2 -5%.…”
Section: Strategies For Efficient Prebiotic Oligosaccharide Productionmentioning
confidence: 98%
“…In line with this view, additional exo-acting enzymes (␤-mannosidases and ␣-galactosidases) or sugar phosphorylases (35) are likely to be needed to complete the degradation to monomers. An ␣-galactosidase from B. adolescentis has been expressed recombinantly (61). Its potential activity toward galactosyl substitutions of mannosides has, however, not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…From the structural point of view, the direct comparison through multiple-sequence alignments of liquefying and saccharifying enzymes, as well as maltogenic amylases, neopullulanases, and CGTases, that have important transglycosylation activities has allowed the identification of residues potentially involved in transglycosylation activity (20,30,54). In spite of the fact that the ␣-amylase AmyA from T. maritima is already a saccharifying enzyme, after a sequence and structure comparison, we were able to identify various residues that are important in saccharifying amylases and are not conserved in the T. maritima ␣-amylase, suggesting that their mutation may generate an even more saccharifying enzyme; actually, as alcoholysis can be considered a specific type of transfer reaction, this would probably result in a more alcoholytic enzyme.…”
mentioning
confidence: 99%
“…Several reports in the literature indicate that transglycosylation activity can be introduced or modified by promoting the effective concentration of less polar substrates in the active site, either by decreasing the affinity for water (7,20,34) or by modifying the geometry of the active site to disable the activation of the catalytic water molecule (39) and thereby favoring the activation of other, bulkier acceptor groups. The importance of aromatic residues in substrate binding at the active site of glycosidases through stacking interactions is well documented (7), and it has been proven that the introduction or substitution of these kinds of residues can modify the affinity of the protein at the different substrate subsites, affecting both the product profile and the activity of the enzyme (40,45,50,54).…”
mentioning
confidence: 99%